Developing a Stability Indicating Ultra Performance Liquid Chromatographic Method for Simultaneous Quantitation of Degradation Products of Telmisartan and Hydrochlorothiazide in Combination Dosage Form - Narasimha Reddy G. P.; Sreenivasulu Reddy T.; Sidda Reddy K.; Shashi Kumar K. N. (Advanced Concepts in Pharmaceutical Research Vol. 9, 2024)
Telmisartan (TLM) is an angiotensin receptor blocker (ARB) that has an extensive period of working and has the lengthy half-life of any ARB. Telmisartan works by blocking a substance in the body that causes blood vessels to tighten. This work is intended to thrive a stability-indicating Ultra performance liquid chromatographic method for the estimation of Telmisatam (TLM) and Hydrochlorothiazide (HCTZ) and degradation products pharmaceutical dosage forms. Separation was carried out on Zorbax Eclipse XDB C-18(50 x mm, 1.7 µm) column using a gradient method. Mobile phase A is 10mM KH2PO4 having 1% (v/v) of trimethylamine and mobile phase B is acetonitrile used in this work. 0.5 mL/ minute is the flow rate and at 271 nm noticed wavelength is monitored. Method development trails were carried out on six different columns. For specificity, limit of quantification, limit of detection, linearity, accuracy, method precision, robustness and stability this method is validated. The correlation coefficient of the impurities is more than 0.99. The stability indicating method confirmed that there was no interference of all impurities of TLM and HCTZ. TLM and HCTZ tablet samples stored and long-term storage conditions. The effect of storage conditions results proved that the method has stability indicating capability. Hence, the developed LC method was stability indicating and well applied for drug product stability study as well as for quality monitoring.